Analysis of the Impact of Patriarchal Culture on the Role of Women in Politics and Governance - Idrus, Iqbal Aidar; Anurlia, Siti; Fadiyah, Dina (Jurnal Studi Ilmu Pemerintahan, 2023)
Women's representation in politics was echoed since July 7, 1954, by the United Nations Convention on Women's Political Rights. In Indonesia, the birth of Law No. 68 of 1958 established the State Ministry for Women's Affairs in 1978 and ratified the Convention on Women's Political Rights to function to improve women's finances, health, and welfare education. However, it was only in 2003 that the government included a minimum of 30% representation of women in the registration of legislative candidates in Law no. 12 of 2003. Various supports, government regulations, and intense campaigns by feminist activists have not directly had an impact on the existence of women in politics and other fields. The birth of Patriarchal Culture in ordinary society towards both men and women has an impact on the social and political aspects of society and contributes to the achievement of gender equality. This is the background for the author to analyze the impact of patriarchal culture on the role of women in politics. This article uses a literature review approach by collecting several reading sources, both scientific journals and books, and laws. Based on the results of the analysis, there are several impacts from the development of patriarchal culture in society, namely: (1) Marginalization, (2) Subordination, (3) Stereotypes, and (4) Violence. Women who are required to take care of the house, children, and family influence the parenting style of girls. Thus, affecting the representation of women in national political contestation in parliament.